Parental Job Loss and Application Decisions in Finnish Post-Secondary Education - Marja-Lisa Laukkonen (The Research Institute of the Finnish Economy (ETLA), 2018)
In Finland, there are no tuition or application fees for post-secondary education. However, the application and admission processes by which the educational institutions select new students may still generate inequalities between prospective applicants from different socioeconomic backgrounds. Institutions select their students based on school and program-specific entrance examinations that measure how well the applicants have mastered predetermined exam materials. Typically, preparing for the exams is time consuming and applicants focus on one entrance exam at a time. Selectivity varies between the schools and programs, depending on the exam performance of the competing applicants. As a result, it can be difficult for students to evaluate their chances of being selected. This uncertainty together with the limited number of applications introduces a strategic component to the application decisions. Furthermore, students from low-income families may not have the resources to take preparation courses or to cover the costs of spending gap years to prepare for the exam. To study the socioeconomic aspect of application decisions, I use information on the newly graduated Finnish general upper secondary school students between the years 2004 and 2013. First, I document differences in application behaviors between students from different family income groups. Students who have performed equally well on the Finnish language test in the national matriculation examination but come from different family income groups exhibit different application behaviors. Compared to their peers from high-income families, students from low-income families are less likely to apply to universities and more likely to apply to polytechnics, send fewer applications overall, and apply to less selective programs. Second, by exploiting information on parental job losses due to plant closures, I investigate the causal impact of family income on the application decisions. I find that parental job losses have no impact on the likelihoods of high school graduates applying to any post-secondary institution, to at least one university or to at least one polytechnic. Instead, the affected students change their application strategies by sending fewer applications and by choosing less selective programs.
Keywords: I23; I24; 330; Economics; Post-secondary education; Application strategies; Parental job loss